2020
DOI: 10.1029/2019jg005217
|View full text |Cite
|
Sign up to set email alerts
|

Salinity Affects Topsoil Organic Carbon Concentrations Through Regulating Vegetation Structure and Productivity

Abstract: Estuarine salt marshes have been recognized as one of the most efficient carbon sinks in the biosphere, with considerable potential for climate change mitigation. However, there are still uncertainties about the response of soil carbon stocks to enhanced soil salinization caused by accelerated sea-level rises and aggravated saltwater intrusion. We therefore conducted both field investigations in the Chongming Dongtan salt marsh of the Yangtze River Estuary, China, and manipulative experiments on marsh soils oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…For example, the primary productivity of S. alterniflora varies with climatic conditions (Kirwan et al, 2009; Xu et al, 2020), resulting in highly variable invasion effects on SOC content among different climatic zones. Specifically, the invasion of Phragmites australis ‐dominated salt marshes by S. alterniflora has been shown to increase SOC content in the northern subtropics (Bu et al, 2015; Xue et al, 2020) but decrease SOC content in warm temperate climate zones (Zhang et al, 2021). The changes in primary productivity that occur following S. alterniflora invasions also vary with ecosystem type (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the primary productivity of S. alterniflora varies with climatic conditions (Kirwan et al, 2009; Xu et al, 2020), resulting in highly variable invasion effects on SOC content among different climatic zones. Specifically, the invasion of Phragmites australis ‐dominated salt marshes by S. alterniflora has been shown to increase SOC content in the northern subtropics (Bu et al, 2015; Xue et al, 2020) but decrease SOC content in warm temperate climate zones (Zhang et al, 2021). The changes in primary productivity that occur following S. alterniflora invasions also vary with ecosystem type (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Elevations determine the spatial extent of marsh expansion by opening the first "windows of opportunity" (Balke et al 2014;Hu et al 2015b;Fivash et al 2021). Low elevations that result in high inundation frequency lead to seedling death due to physiological stress (Cui et al 2020;Xue et al 2020). Sufficient habitats with moderate inundation frequency at N-site helped accommodate new scattered patches, while new marshes at S-site would enlarge in size by merging into the existing ones in the narrow space above MHNW.…”
Section: Discussionmentioning
confidence: 99%
“…These biogeochemical processes are distinctly different from terrestrial ecosystems. Vegetation growth is a critical aspect of developing ecosystem functions for coastal estuarine wetlands. ,, Soil salinization reduces water availability to wetland plants, thereby inhibiting plant growth, soil fertility, and biodiversity. …”
Section: Discussionmentioning
confidence: 99%
“…Vegetation growth is a critical aspect of developing ecosystem functions for coastal estuarine wetlands. 2,52,53 Soil salinization reduces water availability to wetland plants, thereby inhibiting plant growth, soil fertility, and biodiversity. 54−56 The results of PCA combined with RF analyses (Figure S7a,b, respectively) suggested that soil salinity influenced plant species and vegetation communities in the studied wetland soils.…”
Section: Salinity-mediated Vegetation Establishmentmentioning
confidence: 99%